(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-50-64 The article focuses on the study of modern English small-format texts, namely it aims to determine a set of their typological features. The interest in the topic stems from the fact that in present-day English there is a distinct tendency towards minimization of textual volume; as a result, various types of short texts circulate in great quantities in all the spheres of communication, including science, media, education, business, literature, personal interaction, etc. The sheer quantity of such texts yields an assumption about the emergence of a qualitatively new phenomenon, a special type of texts – small-format texts. They possess a specific set of common mechanisms by means of which they successfully perform their pragmatic function with the help of a limited number of language means; these mechanisms need to be elicited and analyzed. This aim is addressed in the article through the analysis of a significant scope of the scattered linguistic data from the current researches on the relevant topic; also an empirical base of approximately 5000 textual samples belonging to different types of discourse is analyzed. As a result, a set of typological features of small-format texts is determined. One of the key features is the visual integrity of small-format texts, which plays a consolidating role in the process of forming the overall semantics of the texts. Apart from that, the typological parameters include the minimization of the exponential plane; a specific type of the surface structure compression consisting in its multi-layer organization; asymmetry of the exterior and interior (semantic) planes; hierarchization of the functional paradigm; rigidity in the choice of structural and/or content elements within one concrete genre; polycode character, as well as lability of the language norm. Key words: small-format text, text type, typological features, expression plane, content plane, functional paradigm, integrity, compression, polycode character, language norm